Relationship Network Analysis of Manufacturing System Limited by Business Lines - CHEN Guorong; DENG Juli; SHI Jinliang; YAN Ping (Institute of Advanced Engineering and Science, 2012)
It is a common problem of manufacturing enterprise limited by business line, which optimized its resources allocation to increase productivity, but now the researches are very weak in relationship mapping and network analysis method in the world. Aimed to the demands, proposed a resource allocation method limited by business line of manufacturing system based on the relational mapping of production system, manufacturing model of hierarchical network based on business line and node degree are been established. Defined the data structure of node on hierarchical network, simplified the network computing by dividing it to three parts - orders assignment, accomplish feedback and pure information exchange. Analyzed the distributing of network degree, established an equation of power law which has two limited parameters of node degree and side weight to automatic compute the amounts of resources of new order. Case study shows that the network analysis method limited business line proposed in the paper can give us an important reference frame of resources assignment. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1415